The increase distance of communication for Wimax system - Vygivskiy, Roman (Видавництво Львівської політехніки, 2010)
In the absence of "direct visibility" (mode NLOS), at high frequencies and at high data rates that are typical for systems of WiMAX, the size of the coverage area for base station can be very small. In these circumstances, to ensure the required distance to the subscriber and the necessary information capacity can be used wireless relay lines.
Keywords: intersymbol interference; interchannel crosstalk; many flights of broadcasting line